IMPLEMENTAÇÃO DE TECNOLOGIAS PARA ANÁLISE E VISUALIZAÇÃO DE DADOS DO SETOR PORTUÁRIO E AQUAVIÁRIO DO MARANHÃO: UMA ABORDAGEM INOVADORA PARA A TRANSFERÊNCIA DE TECNOLOGIA - OLIVEIRA, Francisco Jadson Brito de (2024)
This study proposes two products for the analysis and visualization of data related to the port and waterway sector in the state of Maranhão, Brazil. The initiative involves creating a technical report and an interactive virtual dashboard focusing on this sector. Both products are designed to provide a clear and accessible overview of relevant sector data. Data for this study were extracted from the Estatístico Aquaviário compiled by the Agência Nacional de Transportes Aquaviários (ANTAQ), covering the period from 2010 to 2022, which will allow for an analysis of trends and patterns in the sector over time. The proposed approach for data analysis adapts the Wickham and Grolemund (2019) workflow, focusing on importing, tidying, transforming, visualizing, and communicating data, enabling an in-depth and comprehensive exploration. The R programming language will be used for data cleaning and organization. PostgreSQL will be employed as the Relational Database Management System. The Power BI tool will be used to build the interactive dashboard, providing an intuitive and user-friendly platform for analyzing sector data. This initiative represents a technology transfer process from the university to support management processes within the port sector.